Stereotactic radiosurgery combined with immune checkpoint inhibitors or kinase inhibitors for patients with multiple brain metastases of malignant melanoma. Issue 2 (April 2019) - Stera, Susanne; Balermpas, Panagiotis; Blanck, Oliver; Wolff, Robert; Wurster, Stefan; Baumann, Rene; Szücs, Marcella; Loutfi-Krauss, Britta; Wilhelm, Maria-Lisa; Seifert, Volker; Rades, Dirk; Rödel, Claus; et al.
Abstract : The aim was to evaluate toxicity and oncological outcome of combined stereotactic radiosurgery (SRS) and immunotherapy or targeted therapy in patients with multiple brain metastases originating from malignant melanoma. Despite the fact that both SRS and kinase inhibitors or immune checkpoint inhibitors are considered standard treatment options for this indication, the optimal combination and sequence of these modalities remains largely unknown, especially for patients with a high number of brain metastases. For this retrospective analysis, conducted in two large SRS dedicated centers, we identified patients with brain metastases from malignant melanoma and simultaneous application of immunotherapy or targeted therapy within 30 days of SRS. Forty-eight patients with a total of 250 lesions (median: 3) were treated in 65 single fraction SRS sessions from 2012 to 2018. After a median follow-up of 8.3 months (range: 1.2–43.6 months), the 6-month and 1-year overall survival rates were 75.3 and 50.8%, respectively. The local control rate at one year was 89.5%. Immunotherapy and the application of systemic treatment directly before or concomitant to SRS were both associated with improved overall survival ( P =0.037 and 0.045, respectively). We observed four grade III toxicities, of which only two can be clearly attributed to the combined treatment. Various combinations of SRS and kinase inhibitors or immune checkpoint inhibitors appear feasible and provide promising oncological results and safety profiles for treating few ( n =1–4) and also multiple ( n ≥5) melanoma brain metastases.